The heart of the adult goldfish Carassius auratus as a target of Bisphenol A: a multifaceted analysis. (15th January 2021) - Filice, Mariacristina; Leo, Serena; Mazza, Rosa; Amelio, Daniela; Garofalo, Filippo; Imbrogno, Sandra; Cerra, Maria Carmela; Gattuso, Alfonsina
Abstract: Bisphenol A (BPA) is a contaminant whose presence in aquatic environments is increasing. In fish embryos and larvae, it severely affects cardiac development; however, its influence on the heart function of adult fish has been scarcely analyzed. This study investigated the effects of the in vivo exposure to BPA on heart physiology, morphology, and oxidative balance in the goldfish Carassius auratus . Adult fish were exposed for 4 and 10 days to two BPA concentrations (10 μM and 25 μM). Ex vivo working heart preparations showed that high concentrations of BPA negatively affected cardiac hemodynamics, as revealed by an impaired Frank-Starling response. This was paralleled by increased cardio-somatic indices and by myocardial structural changes. An altered oxidative status and a modulation of stress (HSPs) and pro-apoptotic (Bax and Cytochrome C) proteins expression were also observed in the heart of animals exposed to BPA, with detrimental effects at the highest concentration and the longest exposure time. Results suggest that, in the adult goldfish, BPA may induce stressful conditions to the heart with time- and concentration-dependent deleterious morpho-functional alterations. Graphical abstract: Image 1 Highlights: BPA exposure impaired the hemodynamic performance of the goldfish heart. Cardiac structural changes were observed after BPA exposure. BPA affected oxidative state and expression of stress and pro-apoptotic markers. Abstract : By using a multilevel experimental approach, the study demonstrated that, in the adult goldfish, BPA affects cardiac hemodynamics, myocardial morphology, and oxidative status.